PELATIHAN SENI KALIGRAFI UNTUK MENINGKATKAN KREATIVITAS ANAK DI DESA RIDOGALIH - Nafiah, Nafiah; Ekowati, Ekowati; Nadhirah Qintharah, Yuha (Universitas Islam 45 Bekasi, 2024)
TPQ Nurul Karomah is a place of religious-based learning located on Hamlet 2. Ridogalih Village, Cibarusah District, Bekasi Regency Learning at TPQ Nurul Karomah is carried out every day in the afternoon or evening. The children of TPQ Nurul Karomah still lack the ability to understand the art of Islamic calligraphy, because basically at TPQ Nurul Karomah itself there has not been any implementation or even special calligraphy art training for TPQ Nurul Karomah children. There the teachers only applied the laws of tajwid, mufrodat in Arabic, and memorized short letters of the Koran. Based on the problems at TPQ Nurul Karomah, the author was motivated to carry out training activities in the art of Islamic calligraphy, with the aim of increasing children's creativity at TPQ Nurul Karomah. The service method carried out by the author is in the form of calligraphy art training which has 3 stages, namely the preparation, implementation and evaluation stages. The training program itself was carried out at TPQ Nurul Karomah involving 30 children, as the main subjects in this program. The results of the service show that community service activities have an impact, namely (1) Increasing the creativity of Ridogalih village children in writing Arabic through the art of calligraphy (2) can have a positive impact on children in developing their creativity, because carrying out this activity can provide a good understanding to TPQ children by holding training.